Peran Pola Numerik Terhadap Semantik Kata "Al-Qalam" Dalam Al-Qur'an - Amni Luthfiani; Sofyan Sauri; Shofa Musthofa Khalid (PAI RAFAH, 2024)
The recurrence of words in the Qur'an, including al-Qalam, demonstrates a divine wisdom and numerical pattern. This study investigates the numerical patterns associated with the word al-Qalam in the Qur'an and its semantic implications. Using J.R. Firth's semantic theory and An-Naufal's approach to numerical miracles, the research explores the interplay between these patterns and the educational, revelatory, and intellectual roles of al-Qalam. This qualitative research employs a descriptive-analytical method. Primary data includes verses containing al-Qalam analyzed through the Qur'anic text and tafsir references, while numerical data were processed using Euclid's greatest common divisor (GCD) method to identify patterns. Results reveal that al-Qalam symbolizes education and the continuity of divine knowledge. Its numerical patterns, such as the GCD 1 found in related words and frequencies, reflect the interconnectedness of educational elements of teacher, student, and knowledge and reinforce the semantic interpretation of al-Qalam. These findings highlight the word's centrality in educational contexts, knowledge transmission, and technological advancements in writing. By integrating numerical and semantic analyses, this study contributes to understanding al-Qalam as a profound symbol of knowledge in the Qur'an, demonstrating its linguistic and mathematical harmony. These insights affirm the Qur'an's structural and semantic depth, offering new perspectives in linguistic and religious studies